Evaluasi Program Bantuan Produktif Usaha Mikro Di Provinsi Riau - Abdul Halim; Hasim As'ari; Adianto Adianto (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The presence of Covid-19 has caused a decline in the economy of the Indonesian people, including Riau Province. One form of effort made by the government in overcoming these problems is by implementing the Micro Business Productive Assistance Program. The purpose of this program is as a form of government assistance in driving small community businesses to revive the Indonesian economic system. This research uses a qualitative method with a case study approach. While the acquisition of data from this research was obtained interviews and from previous research materials. Research informants were obtained using purposive sampling method. The results of this study show that the Micro Business Productive Assistance Program in Riau Province, especially in Pekanbaru City, has not run optimally according to the CIPP evaluation model. The context of the program showed that the government seemed to impose the program without readiness, which led to changes in the Regional Regulation and input mismatches. Program implementation did not achieve the initial target set by the government. The productivity criterion shows that the grants were misused for personal gain. The obstacles in this program are the lack of information conveyed to business actors about the productive assistance program for micro businesses, low community access to technology, and the low quality of human resources.